Intussusception in an Infant With SARS-CoV-2 Infection: A Case Report and a Review of the Literature - Castellazzi, Massimo Luca; Corsello, Antonio; Cerrato, Lucia; Carnevali, Alessandra; Morandi, Anna; Leva, Ernesto; Agostoni, Carlo Virginio; Marchisio, Paola (Frontiers in Pediatrics, 2021)
Coronavirus disease 2019 (COVID-19) is caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Even if predominantly considered a respiratory pathogen, it could be associated with gastrointestinal involvement, generally in mild forms. Recent reports highlight the association between SARS-CoV-2 and intussusception in infants. A case of intussusception is hereby described in a previously healthy infant in whom the diagnosis of SARS-CoV-2 was made after the analysis of bronchoalveolar lavage and intraoperative specimens following surgical procedures. Accordingly, a review of infant cases with intussusception and SARS-CoV-2 infection is also reported.